The effect of Lactobacillus with prebiotics on KPC-2-producing Klebsiella pneumoniae - Tang, Hung-Jen; Chen, Chi-Chung; Lu, Ying-Chen; Huang, Hui-Ling; Chen, Hung-Jui; Chuang, Yin-Ching; Lai, Chih-Cheng; Chao, Chien-Ming (Frontiers in Microbiology, 2022)
Objectives: This study investigated the inhibitory effect of Lactobacillus spp. with prebiotics against Klebsiella pneumoniae carbapenemase-2 (KPC-2)-producing Klebsiella pneumoniae using both in vitro experiments and animal models. Methods: Thirty-three Lactobacillus spp. strains were confirmed by 16S rDNA sequencing, and four different PFGE genotyped KPC-2-producing K. pneumoniae strains were selected for investigation. In vitro studies, including broth microdilution assays, changes in pH values in lactobacilli cultures with different prebiotics, time-kill tests of Lactobacillus spp. against KPC-2-producing K. pneumoniae and further in vivo Lactobacillus alone or in combination with prebiotics against KPC-2-producing K. pneumoniae in an animal model, were performed. Results: The lower pH value of the cell-free supernatant was associated with a lower minimal inhibitory percentage of the Lactobacillus strain against KPC-2-producing K. pneumoniae. Furthermore, lactulose/isomalto-oligosaccharide/inulin and fructo-oligosaccharide can enhance the inhibitory effect of all 107 CFU/mL Lactobacillus strains against KPC001. Three Lactobacillus strains (LYC1154, LYC1322 and LYC1511) that could be persistently detected in the stool were tested for their ability to reduce the amount of KPC001 in the feces individually or in combination. A significantly better effect in reducing the amount of KPC001 was observed for the combination of 3 different Lactobacillus species than for each of them alone. Furthermore, their inhibitory effect was enhanced after adding lactulose or isomalto-oligosaccharide (both p < 0.05). Conclusions: This study demonstrates the inhibitory effect of probiotic Lactobacillus, including LYC1154, LYC1322 and LYC1511, with prebiotics such as lactulose or isomalto-oligosaccharide against the colonization of KPC-2-producing K. pneumoniae. moniae.